Cultivo de plantas de milho (Zea mays) com diferentes espaçamentos entrelinhas para produção de silagem - Oliveira, Dierle Tubiana de (2022)
Corn (Zea mays) represents one of the main commodities grown in Brazil, being a nutritional source for ruminant animals, through the use of silage. Thus, silage is the most common practice for the conservation of corn forage, considering its ease of storage and its acceptance by ruminant animals. The morphological structure of corn is that of a large plant and this makes it a climatically demanding crop, thus, when compared to alternative sources of silage, it has higher nutritional quality for animal nutrition. The quality of silage is influenced by its production process, so it can be impacted by factors ranging from the sowing of the cultivar to its storage. Therefore, the sowing of the corn crop is extremely important, since it will impact the positioning of the plants in the area and, as it is a crop that does not have tillering as a characteristic, adequate spacing between plants and between rows is essential. essential. In this context, the objective of the present work was to evaluate corn productivity and the chemical composition of its silage, using different corn cultivars with different spacing between rows. Corn cultivation took place in the municipality of Palmeira das Missões-RS, climate type Cfa, soil classified as typical dystrophic red latosol, the experimental design was specific blocks to evaluate four spacings between rows (45, 60, 75 and 90 cm), with three replications for each hybrid. Sowing was carried out on 10/21/2009 and the plants were cut on 02/08/2010, at a height of 15 cm. The parameters of green matter production (GMP) per hectare, number of ears per plant, determination of plant height (m) and height of insertion of the first ear (m) were evaluated. (PMS) per hectare. However, it can be verified that the different spacings between lines do not interfere in the development of the plants. In the chemical composition of the silages, there were alterations that influenced the silageirono hybrid in the content of NIDN, NIDA and cellulose. In the graniferous hybrid, it presented a greater participation of ears and a higher starch content, being able to define in this study that it is the hybrid indicated for more demanding categories such as dairy cows.